2020
DOI: 10.1177/2374373520967807
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Patient Satisfaction on Patient Commitment and the Mediating Role of Patient Trust

Abstract: The purpose of this study is to determine the effect of patient satisfaction on patient commitment and the mediating role of patient trust in this effect. The study was conducted with 595 patients receiving healthcare services from the city center of Sakarya in Turkey. The data were collected between March 30, 2017, and May 29, 2017, via questionnaire method. The Patient Satisfaction Scale by Chang et al, the Patient Commitment Scale by Torres et al, the Patient Trust Scale by Ozawa, and an Introductory Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…(There is a statistically significant correlation between the quality of service and patient satisfaction), with the results indicating an average relationship of (0.503). From the above, it can be said that accepting the right hypothesis imposed (there is a correlation between trust and patient satisfaction), is consistent with the findings of the study [56] and study [61]. The results of Table 10, shown in Figure 4, show an incorporeal impact of trust factors on patient satisfaction, and this finding is consistent with studies [62] and study [63] and study [64] as indicated by the calculated value (F) of (126.727) which is greater than the scheduling value (1.64), to show the explanation of the confidence factors related to (communication, Competence, and quality of service, which lead to patient satisfaction with the service provided by the researched medical clinics and reality (0.519), the remaining value is not included in the current study model.…”
Section: Figure 2 Structural Model Of Trust Variablesupporting
confidence: 88%
See 1 more Smart Citation
“…(There is a statistically significant correlation between the quality of service and patient satisfaction), with the results indicating an average relationship of (0.503). From the above, it can be said that accepting the right hypothesis imposed (there is a correlation between trust and patient satisfaction), is consistent with the findings of the study [56] and study [61]. The results of Table 10, shown in Figure 4, show an incorporeal impact of trust factors on patient satisfaction, and this finding is consistent with studies [62] and study [63] and study [64] as indicated by the calculated value (F) of (126.727) which is greater than the scheduling value (1.64), to show the explanation of the confidence factors related to (communication, Competence, and quality of service, which lead to patient satisfaction with the service provided by the researched medical clinics and reality (0.519), the remaining value is not included in the current study model.…”
Section: Figure 2 Structural Model Of Trust Variablesupporting
confidence: 88%
“…This makes it not an easy process to measure because it is related to the psychological state of patients through positive and negative thinking in the minds of patients but extends to their families and general assessment of aspects of service [50]. In the relevant literature, two or two types of patient satisfaction have emerged, the first is known as the satisfaction of the transactions that occur or is expressed through the patient's assessment of his experience of visiting for the first time (immediate realization) of the service provided, while the second is called cumulative satisfaction (general satisfaction) and expressed through the patient's assessment of an experience over time and the visit of the service provider more than once [56]. Patient satisfaction has been linked to many positive results, providing insight and insight into the structure, processes, and results of service delivery, which qualifies it as an indispensable factor when evaluating the service in general [57].…”
Section: Patients Satisfactionmentioning
confidence: 99%
“…We found that a higher level of satisfaction with insurance by patients increased the trust in insurance programs. Recent studies [68][69][70] also proved that increase in patient satisfaction could have a positive impact on patients' trust. Another SEM research on URRBMI enrollees suggested that the perception of policy quality was a decisive factor in the perceived quality of URRBMI [20].…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the association between patient trust and patient satisfaction may not be surprising given that the conditions of good will and future cooperation inspire both satisfaction and trust. For example, Durmus and Akbolat (2020) examined the potential impact of patient satisfaction on patient commitment with patient trust as a mediator. Their analysis supports the idea that patient trust is an antecedent of patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%